Constructing Narrative Identity and Capabilities of Finnish Reform School Adolescents - Niiranen Janette; Isola Anna-Maria; Känkänen Päivi; Manninen Marko (SPRINGER, 2022)
Most studies of adolescents placed in foster care due to severe conduct problems have focused on their problems, while adolescents with healthy adulthood condition remain understudied. In Finland, adolescents with severe conduct problems are placed in reform schools (RS). The purpose of this study was to examine how former RS adolescents' narrative identity and capability construction interact in different phases of their life-stories. Semi-structured life-story interviews were conducted with 13 former RS adolescents with healthy adulthood condition. Data were analyzed using a narrative constructivist method. We found a story in which the theoretical elements found from the research material were especially rich and thick and decided to present it as a case example of our findings-Anna's story. The analysis showed that capabilities were closely related to RS adolescents' identity construction and well-being. Strengthened capabilities provided material for identity construction, such as identities of meaning making, agency, redemption, and communion. The findings of the study point out that out-of-home care adolescents' stable and trusting relationships should be supported as they may strengthen capabilities and help develop feelings of meaningfulness, belonging, experienced parity of participation and senses of coherence.